Peningkatan Estetika Objek Wisata Pesona Tanjung Malaha Kecamatan Samaturu Guna Menambah Daya Tarik Wisatawan - Irmayanti, Irmayanti; Zizih, Andi Rezah Tenri; Aldy, Muh.; Maulana, Muh. Veri; Mutmainna, Andi; Sari, Nadia; Syaiful, Muhammad; Sapriyadi, Sapriyadi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The aim of this service is to improve the aesthetics of the Pesona Tanjung Malaha tourist attraction in Malaha Village, Samaturu District, Kolaka Regency, in order to increase its tourist attraction. The method used is participatory and collaborative, inviting the community to play an active role. Activities start with field observations, interviews, coordination, and formulating alternative solutions. The activity stages include: (1) field observations at tourist locations; (2) interviews and coordination; (3) formulating alternative solutions; (4) painting signboards, cleaning beaches, and planting sea pine and sea pandan trees; and (5) evaluation of visitor behavior. The results of the activity show that the aesthetics of the tourist attraction have increased significantly. Painting signboards and landscaping helps create a more attractive environment for tourists. In conclusion, efforts to restore and rearrange tourist attractions, including painting signboards, are effective steps to improve the aesthetics of Tanjung Malaha Charm, which is expected to attract more tourists to the area.